Avaliação dos desreguladores endócrinos nas estações de tratamentos de esgotos e água - Soares, Manoel Barbosa (2016)
The toxicology of endocrine disruptors (ED), known as micro-pollutants, disposed in the environment through urine or excrements may cause physiological changes in aquatic living things. Therefore, it was aimed to evaluate the 17β – estradiol (E2) and progesterone and measure the quality of the wastewaters from the effluent of some Sewage Treatment Plants (STP’s) as of potable water in the Water Treatment Plant (WTP), located in Goiânia – GO, through the physical and chemical parameters, such as: Potential Hydrogen (PH), Temperature (T), Electric Conductivity (EC), Turbidity, Total Dissolved Solids (TDS), Salinity, Dissolved Oxygen (DO), Total Organic Nitrogen, Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (BOD). The quantization of endocrine disruptors was obtained through direct and competitive ELISA’s method, and all physical-chemical parameters were determined based on the APHA's Manual (2012). The effluent samples were collected at three distinct points: affluent (raw sewage), confluence of the effluent to the river (CER) and downstream of the release in STP’s Hélio Seixo de Brito (HSB), Samambaia (S) and Parque Atheneu (PA), while the samples of potable water were collected at two different points: in the capture of João Leite’s stream and after the water treatment in the WTP Jaime Câmara (JC). Through the physical-chemical parameters evaluated in the STP’s , the Turbidity , both DO and BOD, do not agree with the standards of CONAMA 357/05 and 430/11, which means that a lot of organic and inorganic matter are being dumped into the Meia Ponte River without treatment. In relation to the JC’s WTP, the same physical-chemical parameters are in accordance with the Decree No. 2,914 / 11 from the Ministry of Health, which deals with drinking water quality. The measured values for the E2 in the STP’s ranged in the rainy season around 53, 7 to 178, 24 ng/L and 45, 8 to 275, 0 ng/L in the dry season. In contrast with the progesterone in the same place where the values ranged from 69, 34 to 97, 54 ng / L in the rainy season from 60, 2 to 603, 8 ng / L in the dry season. While in the Meia Ponte River these values to the E2 ranged between 2,04 to 31,62 ng / L in the rainy season from 6,02 to 72,44 ng / L in the dry season and in relation to progesterone 4,35 to 52,48 ng / L in the rainy season 6,6 to 218,25 ng / L in the dry season. At João Leite’s stream, where is made the abstraction of the water for treatment, both in the rainy and drought seasons, E2 values were found 2,13 and 4,89 ng / L and progesterone 5,37 and 6,76 ng / L, however, the treated water that leaves the ETA, it was found in it values of E2 1,81 ng / L and 2,51 ng / L and progesterone 4,78 ng / L and 4,67 ng / L during the rainy and dry seasons, respectively. This search concludes that the biological method ELISA was efficient for the quantification of the studied hormones, and the values found for both the E2 and progesterone to the STP’s and ETA was xvii greater than 1.0 ng / L, and according to the literature these values are able to cause physiological damage in aquatic species.